Study on the Testing Method for Marine Diesel Engine - Miaofen Zhu; Guojin Chen; Zhongmin Liu; Tingting Liu; Shaohui Su; Yijiang Cao (Institute of Advanced Engineering and Science, 2014)
For the high-power low-speed diesel engine’s performance and reliability evaluation, this paper studies the engine’s running-in norms, presents the Test Scheme about the combustion process, the Inlet swirl control, the cooling system control, and the distribution and emission. The whole engine’s test methods and systems are established. By using the combined method of the test platform research and the theoretical model analysis, the diesel engine’s performance and reliability tests are made to evaluate the engine’s design. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4212